2022
DOI: 10.5155/eurjchem.13.1.69-77.2188
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of a single-walled carbon nanotube and a cellulose biofiber as 5-fluorouracil anti-cancer drug carriers

Abstract: Chemotherapy is one of the most valuable and widely available option in cancer treatment. However, a method of delivering the drug to achieve a therapeutic effect still a considerable challenge. Therefore, this study seeks to identify the non-bonding interaction of 5-fluorouracil anticancer drug with a single walled carbon nanotube and a Cellulose bio-fiber using density functional theory and molecular mechanics simulations. To do that, adsorption locator and DMol3 modules were utilized to determine the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…32 Another study has shown that the nickel modification can improve the adsorption of water molecules on anatase-TiO 2 , rutile-TiO 2 , and ZnO photoanodes, enhancing their photoelectrochemical performance. 61 Particularly, Adsorption Locator for modelling has been broadly used for evaluating the adsorption interaction or non-bonded energies of organic and water molecules for various applications, including biomolecule/surface interactions, 62 adsorption of SiF 4 and HF gaseous molecules at the molecular level, 63 next-generation protein-based biosensor surfaces, 64 catalyst/adsorbents for oil recovery and viscosity reduction process, 65 drug delivery tool in biological systems, 66 etc. Here, the influence of the Al 3+ –Mg 2+ dual substitution on the adsorption of water molecules on the BaTaO 2 N(110) surfaces was also explored by combined Molecular Dynamics and Monte-Carlo computer simulation.…”
Section: Resultsmentioning
confidence: 99%
“…32 Another study has shown that the nickel modification can improve the adsorption of water molecules on anatase-TiO 2 , rutile-TiO 2 , and ZnO photoanodes, enhancing their photoelectrochemical performance. 61 Particularly, Adsorption Locator for modelling has been broadly used for evaluating the adsorption interaction or non-bonded energies of organic and water molecules for various applications, including biomolecule/surface interactions, 62 adsorption of SiF 4 and HF gaseous molecules at the molecular level, 63 next-generation protein-based biosensor surfaces, 64 catalyst/adsorbents for oil recovery and viscosity reduction process, 65 drug delivery tool in biological systems, 66 etc. Here, the influence of the Al 3+ –Mg 2+ dual substitution on the adsorption of water molecules on the BaTaO 2 N(110) surfaces was also explored by combined Molecular Dynamics and Monte-Carlo computer simulation.…”
Section: Resultsmentioning
confidence: 99%